PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN LAGU DAERAH SETEMPAT UNTUK MOTIVASI BELAJAR SISWA DI SMP 1 NEGERI RANAH PESISIR - Shadila Deykisy; Ardipal Ardipal; Syeilendra Syeilendra (SENDRATASIK UNP, 2014)
Abstract This type of study is a qualitative study using descriptive analysis and the main instrument is the author of his own with the use of data collection techniques including observation, interviews and literature study and several tools to collect data in the field such as stationery, hp cameras, digital cameras. From the research Use of Audio Visual Media In Learning Locally Songs To Improve Student Motivation In Class VII SMP Negeri 1 Coastal Domains. Instructional media used in SMP Negeri 1 Domains Coastal VII class on learning the art of music, especially the song material is a local area of ​​audio and visual. In the early stages of research looks KLS VII student motivation is very low in the study of local songs. Many things that cause it, such as media selection and learning improper influences from outside. After doing research for 6 sessions in class VII akirnya authors obtain research results. Results illustrate an increase in students' motivation in learning local songs, it is evident from the teaching and learning activities in the classroom such as: students were enthusiastic in watching video song displayed local teachers, students observe local song video shown, students work on assignments per group, the student arranges the songs in a simple local area and per group, students display the results of the local arrangements of folk songs with kreativ and expression very good in front of the class. From the results of the research can be seen increasing students' motivation in learning local songs using audio-visual instructional media.   Kata kunci: Pengunaan, media audi visual, lagu daerah setempat, motivasi.